Mild‐to‐severe poisoning due to Conium maculatum as toxic herb: A case series - Boskabadi, Javad; Askari, Zahra; Zakariaei, Zakaria; Fakhar, Mahdi; Tabaripour, Rabeeh (Clinical case reports, 2021)
Conium maculatum toxicity may occur by mistakenly or intentionally eating this plant. Due to muscarinic or nicotinic symptoms associated with this plant toxicity, supportive care and treatment with atropine are urgently important. Conium maculatum toxicity may occur by mistakenly or intentionally eating this plant. Due to muscarinic or nicotinic symptoms associated with this plant toxicity, supportive care and treatment with atropine are urgently important.